Dieting and Food Cue-Related Working Memory Performance - Meule, Adrian (Frontiers in Psychology, 2016)
Executive functioning (e.g., working memory) is tightly intertwined with self-regulation. For example, food cue-elicited craving has been found to impair working memory performance. Furthermore, current dieters have been found to show lower working memory performance than non-dieters. Recent research, however, suggests that it is crucial to consider dieting success in addition to current dieting status or restrained eating in order to reveal cognitive mechanisms that are associated with successful eating-related self-regulation. The current study investigated food cue-related working memory performance as a function of dieting status and dieting success in female students. Participants performed an n-back task with pictures of food and neutral objects. Reaction time in response to food pictures was slower than in response to neutral pictures, whereas omission errors did not differ between picture types. Current food craving was increased after performing the food block, but not after the neutral block. There was an indirect effect of current dieting status on higher food craving after the food block, which was mediated by slower reaction time to food vs. neutral pictures. Furthermore, higher dieting success was associated with fewer omission errors in the food vs. neutral block in current dieters. There were no relationships of restrained eating with current food craving and task performance. Results further highlight the need to differentiate between successful and unsuccessful dieting in addition to current dieting status or restrained eating when examining possible mechanisms of overeating or successful restraint. Although palatable food cues induce food craving regardless of dieting success, they may boost executive functioning in successful dieters, which helps them to overcome these temptations.